THE IMPLEMENTATION OF THE LEGAL CERTAINTY PRINCIPLE IN DETERMINING THE ABILITY TO MAKE NOTARIAL DEEDS BEFORE A NOTARY - Dewa Gede Aldian Diatnika; I Made Dwi Dimas Mahendrayana (Transpublika Publisher, 2022)
This study aims to find out the legal basis for the ability to make an agreement before a notary and to examine the application of the principle of legal certainty in determining the ability to make a notarial deed. This study uses a normative legal research method with a statutory approach and a conceptual approach. The findings indicate that the legal basis for making an agreement before a notary is stated in Article 39 paragraph (1) of the Notary Position Law (UUJN) and the application of the principle of legal certainty to the ability to make a deed, namely the legal basis refers to the UUJN not the Civil Code. The resolution of the conflict of norms is by using the principle of preference, namely the rules that apply are the rules of the UUJN, while the rules of the Civil Code do not apply.